PERANAN LEMBAGA KEPOLISIAN RESOR (POLRES) DALAM PENERTIBAN PERTAMBANGAN EMAS TANPA IZIN (PETI) DI KABUPATEN KUANTAN SINGINGI - Ain, Nur; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Gold Mining without Permit (PETI) is a mining business carried out by individuals, a group of people, whose operations do not have permits and government agencies in accordance with the applicable laws and regulations. PETI was started by the existence of traditional miners, which later developed due to factors of poverty, limited employment opportunities and business opportunities. On the other hand, weaknesses in law enforcement and legislation regulations that eliminate mining (by) people also contribute to the peacock of PETI. This research was conducted at the Kuantan Singingi police station with a focus on research at the Satreskrim Tipiter Section Unit II. Where other subjects are sub-district officials, village officials, and communities to be used as informants. while the data collection technique is by observation, interviews, and documentation and analyzed with qualitative analysis. The results of the study concluded that the institution of the Kuantan Singingi Resort Police was very instrumental. The factors that influence the role of the resort police in controlling PETI in Kuantan Singingi district are as follows: The absence of a special branch of the UPT handling the PETI problem at Kuantan Singingi Police Station, the many obstacles, challenges and disturbances faced by this Tipiter II unit. The effectiveness of the role of the Forkopimda (Regional Leadership Coordination Forum) in handling PETI, there are even indications of omission from village and sub-district officials.Â Keywords: Roles, Police Institutions, and PETI